Identification of a novel variant in N-cadherin associated with dilated cardiomyopathy - Chen, Yuanying; Sun, Qiqing; Hao, Chanjuan; Guo, Ruolan; Wang, Chentong; Yang, Weili; Zhang, Yaodong; Wang, Fangjie; Li, Wei; Guo, Jun (Frontiers in Medicine, 2022)
Background: Dilated cardiomyopathy (DCM), which is a major cause of heart failure, is a primary cardiac muscle disease with high morbidity and mortality rates. DCM is a genetically heritable disease and more than 10 gene ontologies have been implicated in DCM. CDH2 encodes N-cadherin and belongs to a superfamily of transmembrane proteins that mediate cell-cell adhesion in a calcium-dependent manner. There have been no reports of isolated DCM associated with CDH2 deficiency. Methods: We performed whole-exome sequencing in a 12-year-old girl with non-syndromic DCM and her unaffected parents. Variants in both known DCM-related genes and novel candidate genes were analyzed and pathogenicity confirmation experiments were performed. Results: No pathogenic/likely pathogenic variant in known DCM-related genes was identified in the patient. We found a de novo variant in a candidate gene CDH2 in the patient, namely, NC_000018.9(NM_001792.5):c.474G>C, NP_001783.2:p.(Lys158Asn). CDH2 p.Lys158Asn was found in the conserved domain of N-cadherin, which is associated with hydrolysis of the precursor segment and interference with adhesiveness. Furthermore, we tested the expression and efficiency of cell-cell adhesion while overexpressing the CDH2 Lys158Asn mutant. The adhesion efficiency was considerably reduced in the presence of the mutated CDH2 protein compared with wild-type CDH2 protein, which suggested that the mutated CDH2 protein’s adhesion capacity was impaired. The variant was probably pathogenic after integrating clinical manifestations, genetic analysis, and functional tests. Conclusion: We identified a CDH2 variant in DCM. We observed a new clinical symptom associated with N-cadherin deficiency, and broadened the genetic spectra of DCM.